2021
DOI: 10.3390/brainsci11060736
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CD73/A2AR-Mediated Adenosine Signaling as a Potential Mechanism of Neuroprotective Effects of Theta-Burst Transcranial Magnetic Stimulation in Acute Experimental Autoimmune Encephalomyelitis

Abstract: Multiple sclerosis (MS) is a chronic neurodegenerative disease caused by autoimmune-mediated inflammation in the central nervous system. Purinergic signaling is critically involved in MS-associated neuroinflammation and its most widely applied animal model—experimental autoimmune encephalomyelitis (EAE). A promising but poorly understood approach in the treatment of MS is repetitive transcranial magnetic stimulation. In the present study, we aimed to investigate the effect of continuous theta-burst stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Attenuated neuronal death following iTBS was accompanied by a reduction in pro-inflammatory factors and an increase in anti-inflammatory factors. Anti-inflammatory effects of rTMS have been demonstrated in neurological disorders and animal models ( Aftanas et al, 2018 ; Hong et al, 2020 ; Clarke et al, 2021 ; Dragić et al, 2021c ). Furthermore, rTMS was found to inhibit the polarization of astrocytes toward neurotoxic (A1-like) phenotype ( Hong et al, 2020 ), which are also present in TMT-induced neurodegeneration ( Dragić et al, 2021a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…Attenuated neuronal death following iTBS was accompanied by a reduction in pro-inflammatory factors and an increase in anti-inflammatory factors. Anti-inflammatory effects of rTMS have been demonstrated in neurological disorders and animal models ( Aftanas et al, 2018 ; Hong et al, 2020 ; Clarke et al, 2021 ; Dragić et al, 2021c ). Furthermore, rTMS was found to inhibit the polarization of astrocytes toward neurotoxic (A1-like) phenotype ( Hong et al, 2020 ), which are also present in TMT-induced neurodegeneration ( Dragić et al, 2021a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in experimental autoimmune encephalomyelitis (EAE) have demonstrated significant upregulation of eN/CD73 in spinal cord astrocytes (Dragić et al, 2021; Lavrnja et al, 2009) and the appearance of an alternative eN/CD73 variant(s) during the symptomatic phase of the disease (Jakovljevic et al, 2017; Lavrnja et al, 2015). Since eN/CD73 has no structural isoforms in rat, the variants that are identical at the protein, mRNA, and cDNA levels must represent glycoforms that differ in their carbohydrate content.…”
Section: Discussionmentioning
confidence: 99%
“…Within 15–20 years, the disease takes a progressive course with worsening neurological symptoms due to irreversible demyelination and axonal loss. Markedly lower autoimmune cell recruitment during the progressive phase of MS and the profound activation of microglia suggest a crucial contribution of resident glial cells to irreparable neurodegeneration in diffuse areas of the brain and spinal cord (Keegan & Noseworthy, 2002; Dragic et al, 2021). In active MS lesions, microglial cells lose their homeostatic signature (Zrzavy et al, 2017), assume an amoeboid form, and release proinflammatory mediators, including tumor necrosis factor‐α (TNF‐α), interleukin (IL)‐1β, IL‐6, interferon (IFN)‐γ, and NO, which damage brain tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers showed that cTBS acting on the EAE model (animal model of MS as mentioned earlier) can downregulate the pro-inflammatory mediator interleukin-1β (IL-1β) and upregulate the anti-inflammatory cytokine interleukin-10 (IL-10), thus playing an anti-inflammatory role. At the same time, cTBS can effectively improve the changes of adenosine signal transduction and weaken the reaction state of microglia and astrocytes in the EAE model, showing a strong potential for protection and repair in the treatment of the model ( 39 ). What is more, inflammatory injury in patients with MS can lead to abnormal cortical plasticity.…”
Section: Treatment Of Tms In Msmentioning
confidence: 99%